Linguistic characteristics of phraseological units related to the field of economics in English and Uzbek (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article investigates the linguistic features of phraseological units in economic discourse in English and Uzbek. It examines the structural and semantic characteristics of economic phraseologisms and their role in conveying specialized concepts in both languages. The study explores how idiomatic expressions, metaphorical language, and fixed phrases reflect cultural and contextual differences in economic communication. Through comparative analysis, it identifies similarities and contrasts in the usage, meaning, and translation of these units. The findings deepen the understanding of economic terminology and offer insights for linguists, translators, and learners of both languages.